Mapping of Islamic Bank Financial Distress in Indonesia - Iqbal, Muhammad; Riyadi, Selamet; Sabrianti, Priska; Afidah, Afifah Nur (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2018)
Abstract: Mapping of Islamic Bank Financial Distress in Indonesia. This study aims to identify and analyse the level of financial distress of Indonesian Islamic Bank. The data of this study would be utilised to map the level of financial distress of various Islamic banks. This study also aims to assess the level of financial distress by utilising different methods and compare the result. This study measures the level of financial distress by using three different methods, which are: Altman Modification method, Bankometer and Risk Based Bank Rating. This study uses a comparative descriptive approach with eleven samples of Islamic Commercial Banks in Indonesia during 2010-2016. This study finds that Islamic banks in Indonesia are not indicated to have financial distress, but still have the potential to experience financial distress, where each Islamic Bank has different levels of financial distress with another. The three methods of measuring the level of financial distress have differences in measuring financial difficulties in Islamic banks. Keywords: Islamic bank, financial distress, altman modification, bankometerAbstrak: Pemetaan Tingkat Kesulitan Keuangan Bank Syariah di Indonesia. Penelitian ini bertujuan melihat seberapa besar tingkat kesulitan keuangan yang terjadi pada bank syariah di Indonesia. Data penelitian ini ditujukan untuk memetakan keberagaman tingkat kesulitan keuangan bank syariah serta mencoba membandingkan beberapa metode penilaian kesulitan keuangan bank yang ada pada bank syariah. Pengukuran tingkat kesulitan keuangan menggunakan tiga metode yang berbeda, yaitu: metode Altman Modifikasi, Bankometer dan Risk Based Bank Rating. Metode penelitian menggunakan pendekatan deskriptif komparatif dengan sampel sebelas Bank Umum Syariah di Indonesia selama periode 2010-2016. Hasil penelitian menunjukkan bahwa bank syariah di Indonesia tidak terindikasi mengalami kesulitan keuangan, namun tetap berpotensi mengalami kesulitan keuangan dengan tingkat kesulitan keuangan yang berbeda antara satu bank syariah dengan bank syariah lainnya. Penelitian ini juga menemukan bahwa ketiga metode pengukuran tingkat kesulitan keuangan yang digunakan pada penelitian ini memberikan hasil yang berbeda dalam mengukur kesulitan keuangan pada bank syariah. Kata kunci: Bank Syariah, Kesulitan Keuangan, Altman Modifikasi, Bankometer